Pre-negotiation for an international emission reduction game - Haruo Imai; Mayumi Horie (Fondazione Eni Enrico Mattei (FEEM), 2002)
Based on a result due to Ray and Vohra showing the possibility of inefficiency due to a coalition formation in an international emission reduction game, we consider a possibility of negotiation preceding the negotiation stage, and by means of an example, indicate that the efficiency is restored. In the equilibrium obtained, we observe a potential in which different set of coalition arises in the two stages, which could help explain what is going on in the international negotiation.
Keywords: C78; 330; Prenegotiation; coalition formation; international emission reduction game; Klimaschutz; Verhandlungstheorie; Koalition